2022
DOI: 10.1155/2022/8770510
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acupuncture Combined with Rehabilitation on Chronic Pelvic Pain Syndrome in Females: A Meta-Analysis Running Head—Acupuncture Combined with Rehabilitation on Chronic Pelvic Pain

Abstract: Objective. To investigate the clinical efficacy of this combined treatment for chronic pelvic pain syndrome (CPPS) by meta-analysis. Methods. Relevant articles were retrieved from PubMed, CNKI, Wanfang Data, Web of Science, and Embase, including randomized controlled trials on acupuncture combined with rehabilitation for CPPS in females. Results. A total of 224 articles were retrieved in this study, and 14 studies were finally identified for inclusion. Among them, the treatment group was treated with acupunctu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In order to provide high-quality clinical evidence for acupuncture, many researchers have published a large number of related articles. 61 , 62 A large number of systematic reviews have shown that acupuncture can improve the symptoms and quality of life of patients with CPPS and improve pelvic dysfunction. Whether it is a single intervention or combined with other treatment options, the results are satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…In order to provide high-quality clinical evidence for acupuncture, many researchers have published a large number of related articles. 61 , 62 A large number of systematic reviews have shown that acupuncture can improve the symptoms and quality of life of patients with CPPS and improve pelvic dysfunction. Whether it is a single intervention or combined with other treatment options, the results are satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that traditional Chinese medicine in the form of acupuncture may have a role in the treatment of adenomyosis or relief of the clinical symptoms of adenomyosis [60], and further data are awaited in the near future [61].…”
Section: Alternative Approachesmentioning
confidence: 99%